2021
DOI: 10.1136/bmjresp-2021-001063
|View full text |Cite
|
Sign up to set email alerts
|

Use of peripheral neutrophil to lymphocyte ratio and peripheral monocyte levels to predict survival in fibrotic hypersensitivity pneumonitis (fHP): a multicentre retrospective cohort study

Abstract: The factors determining disease course and survival in fibrotic hypersensitivity pneumonitis (fHP) have not been fully elucidated.The aim of this study was to describe the characteristics of patients with fHP in a real-world cohort and investigate factors associated with worse outcomes. We aimed to explore the use of neutrophil to lymphocyte ratio (NLR) and peripheral blood monocyte levels in predicting mortality.MethodsA retrospective, multicentre, observational UK cohort study.ResultsPatients with fHP were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…We did not determine the specificity of NLR to IPF as opposed to other ILDs. However, we have previously reported that within the ILD cohort from RDE/NB/TS/UHL although high baseline NLR predict outcomes in IPF this was not the case in patients with chronic hypersensitivity pneumonitis 5 . Secondly, the majority of the patients were in the pre-anti fibrotic era and were treated with corticosteroids.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We did not determine the specificity of NLR to IPF as opposed to other ILDs. However, we have previously reported that within the ILD cohort from RDE/NB/TS/UHL although high baseline NLR predict outcomes in IPF this was not the case in patients with chronic hypersensitivity pneumonitis 5 . Secondly, the majority of the patients were in the pre-anti fibrotic era and were treated with corticosteroids.…”
Section: Discussionmentioning
confidence: 82%
“…We have previously reported our initial UCLH internal derivation and validation cohorts, 118 patients, as an abstract 17 . The 515 patients from NB/RDE/TS/UHL were reported as part of a larger cohort comparing basic outcome predictors in IPF versus fHP 5…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, we did not observe the relationship between disease progression or mortality and blood cell count and the combined index. According to a multicenter retrospective study, higher baseline NLR and absolute monocyte counts predict worse survival in IPF but not in fHP (Barratt et al, 2021), highlighting the potential divergence in the underlying mechanisms of these diseases. However, our sample size is smaller than the previous reports for the prognostic role of blood cell counts.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of a specific diagnosis of ILD, patients with an HRCT-documented usual interstitial pneumonia (UIP) pattern or extensive traction bronchiectasis, FVC decline, or older age showed the highest mortality risk (Walsh et al, 2018;Yang et al, 2022). In addition, peripheral blood monocyte counts have been investigated in IPF and other ILDs as a predictor of prognosis (Misharin et al, 2017;Barratt et al, 2021). Although studies have reported findings for individual types of PF-ILDs (for example, SSc-ILD, RA-ILD, other CTD-ILDs, and FHP), limited data are available regarding the PF-ILDs as a whole group (Khanna et al, 2020;Skibba et al, 2020;Orlandi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several large cohort studies report the long-term prognosis of f-HP (again previously described as ‘chronic’) [ 107 , 108 , 109 ], highlighting clinical predictors of age, FVC, and radiologic honeycombing. Such findings are reflected in one study applying the Gender-Age-Physiology (GAP) Index, a prognostic model originally derived in patients with IPF and applied to other non-IPF chronic interstitial lung disease patients including 206 patients with ‘chronic’ HP, noting similar staging and predictive characteristics [ 110 ].…”
Section: Treatment Management and Prognosismentioning
confidence: 99%